Irish politics and social conflict in the age of the American Revolution - O'Connell, Maurice R. (University of Pennsylvania Press, 1965)
In the midst of great expansion and economic growth in the eighteenth century, Ireland was deeply divided along racial, religious, and economic lines. More than two thirds of the population were Catholic, but nearly all the landowners were Anglican. The minority also comprised practically the entire body of lawyers, officers in the army and navy, and holders of political positions. At the same time, a growing middle class of merchants and manufacturers sought to reform Parliament to gain a real share in the political power monopolized by the aristocracy and landed gentry. Irish Politics and Social Conflict in the Age of the American Revolution remains one of the few in-depth studies of the effects of the Revolution on Ireland. Focusing on nine important years of Irish history, 1775 to 1783, from the outbreak of war in colonial America to the year following its conclusion, the book details the social and political conditions of a period crucial to the development of Irish nationalism. Drawing extensively on the Dublin press of the time, Maurice R. O'Connell chronicles such important developments as the economic depression in Britain and the Irish movement for free trade, the Catholic Relief Act of 1778, the rise of the Volunteers, the formation of the Patriot group in the Irish Parliament, and the Revolution of 1782.